Sustained Remission of Child Depression Despite Drift in Parent Emotion Management Skills 18 Weeks Following Parent Child Interaction Therapy –Emotion Development - Luby, Joan (Eur Child Adolesc Psychiatry, 2020)
Whether effects of psychotherapies for depression are sustained after treatment is an important clinical issue. In older depressed children and adolescents such treatments have been shown to be sustained for several months. Rates of remission ranged from 62–69% at 3 months to 1 year in one large scale study. To date there has been no data to inform whether the effects of earlier interventions for depression in the preschool period are sustained. METHODS: To address this, we used data from a randomized controlled trial of a novel early intervention for depression called “Parent Child Interaction Therapy Emotion Development” that has shown efficacy for depression, parenting stress and parenting practices. Participants and their caregivers were re-assessed 18 weeks after treatment completion. All study procedures were approved by the Washington University School of Medicine Internal Review Board prior to data collection. RESULTS: Study findings demonstrated a high rate of sustained gains in remission from depression, decreased parenting stress and parental depression 18 weeks after completion of a trial of PCIT-ED in a population of young children. Parental response to the child expression of emotion, a key treatment target drifted back towards baseline after 3 months. Relapse rates were 17% and predictors of relapse were the presence of an externalizing disorder, a higher number of co-morbid disorders and poorer guilt reparation and emotion regulation measured at treatment completion. DISCUSSION: This extends the body of literature demonstrating PCIT to have sustained effects on targeted disruptive symptom profiles to early childhood depression. This relatively low relapse rate after 18 weeks is comparable or better than many empirically proven treatments for depression in older children.